IMC strategy: Acme’s vision of lead the pharmaceutical market of Bangladesh - Muztba, Syed Abu Ishmam (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.